Tai chi: definition, history, style, principles, and health benefits - Niu, Yantao; Buranarugsa, Rojapon; Kuhirunyaratn, Piyathida (Asia-Pacific Journal of Science and Technology, 2024)
Tai chi, an ancient form of exercise, is receiving increasing attention in today’s health-conscious societies. However, despite the many styles of tai chi, a lack of literature on various schools of tai chi has restricted researchers from conducting more extensive, in-depth research on the fitness benefits of the different schools. In our study, we searched relevant literature published up to April 2023 using the keywords “tai chi” or “taijiquan” in five electronic databases: China National Knowledge Infrastructure (CNKI), Google Scholar, Scopus, PubMed, and Web of Science. This narrative review provides an overview of tai chi’s definition, historical development, lineage system, training principles, training plans, and impacts on health. The results show that tai chi is guided by yin and yang theory and is a sport that promotes physical and mental health through slow, relaxed external exercise performance, combined with focused breathing and internal physical and mental exercise. Developed for 300 years, tai chi has emerged in six major schools: Chen (陈), Yang (杨), Wu (武), Wu (吴), Sun (孙), and He (和)-style tai chi. Tai chi styles have 72 to 108 movements and take 6 to 22 min to practise a complete routine of movements, each with its own characteristic exercise programme. Recent evidence from sports science and medicine has shown that tai chi is beneficial for improving human health and enhancing human function and can serve as a beneficial supplement to disease prevention and management programmes.